UPAYA NON PENAL PENINGKATAN KESADARAN HUKUM MASYARAKAT UNTUK MENGGUNAKAN HELM BERSTANDAR NASIONAL INDONESIA DI POLRES TANAH DATAR - Fitri Dewi Utami (UNES Law Review, 2019)
Article 106 paragraph (8) of Law Number 22 Year 2009 concerning Road Traffic and Transportation states that every person driving a Motorcycle and Motorcycle Passenger must use a helmet that meets Indonesian national standards. The level of legal awareness of two-wheeled riders in the jurisdiction of Tanah Datar police station to use SNI-standard helmets is still low. It can be seen from the increase in traffic violations that do not use helmets in Tanah Datar Regency in the last 2 (two) years from 2017 to 2018. Efforts of Non Penal Satlantas of Tanah Datar Regional Police in Increasing Legal Awareness of Two-Wheeled Riders to Use SNI-Standard Helmets is to continue disseminating information to road users, Extension to the bykers / motorbike clubs about the traffic order carried out in front of Pagaruyung palace. Training on the obligation to use SNI helmets for all motorcycle drivers in Tanah Datar. Patrol is one of the police activities carried out by 2 or more members of the National Police.